2021
DOI: 10.1177/08862605211028284
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to HIV Care and Viral Suppression Comparing Newly Diagnosed Women Living with HIV in Rural Uganda with and without a History of Intimate Partner Violence

Abstract: Intimate partner violence (IPV) is associated with poor HIV care linkage and retention, medication adherence, and viral suppression. However, limited knowledge exists regarding potential mechanisms linking IPV to these outcomes. We aimed to (a) identify the top barriers to accessing HIV care experienced by women living with HIV (WLHIV) who report a history of IPV and have suppressed viral load (VL) versus unsuppressed VL and (b) understand how these barriers influence VL, comparing WLHIV with a history of IPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…6 A range of potential pathways from IPV to reduced engagement in care, adherence, and suppression have been described, including ongoing fear of HIV disclosure leading to hiding medication 7,10 and greater challenges in attending medical appointments because of less control over money and mobility. 7,10 The systematic review, however, only drew on literature from high-income settings in North America and included no studies among younger female patients. More recent work from sub-Saharan Africa has demonstrated similar impacts of IPV on the HIV-treatment cascade, 7,11,12 but without a focus on young women, nor population-based samples.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 A range of potential pathways from IPV to reduced engagement in care, adherence, and suppression have been described, including ongoing fear of HIV disclosure leading to hiding medication 7,10 and greater challenges in attending medical appointments because of less control over money and mobility. 7,10 The systematic review, however, only drew on literature from high-income settings in North America and included no studies among younger female patients. More recent work from sub-Saharan Africa has demonstrated similar impacts of IPV on the HIV-treatment cascade, 7,11,12 but without a focus on young women, nor population-based samples.…”
Section: Introductionmentioning
confidence: 99%
“…5 One key driver of poor engagement in the cascade of HIV care and treatment for women is exposure to intimate partner violence (IPV). 6 Studies suggest among women who experience violence HIV-testing maybe reduced because of fear of disclosure if HIV positive, 7,8 although others suggest testing may increase as women realize they may be more at risk of acquiring HIV. 9 A systematic review found women who experienced IPV were less adherent and had poorer engagement in HIV care and lower odds of viral suppression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is more evidence amongst adult women: a 2015 meta-analysis of 13 cross-sectional studies found that IPV was associated with lower self-reported ART adherence and viral load suppression [ 18 ], with this finding supported by a scoping review in 2019 [ 19 ]. Since these reviews, associations between IPV and nonadherence have been found in cross-sectional studies of adult women in Kenya [ 20 , 21 ], Uganda [ 22 ], and longitudinally in South Africa [ 23 ].…”
Section: Introductionmentioning
confidence: 99%